2016
DOI: 10.1007/s11120-016-0310-6
|View full text |Cite|
|
Sign up to set email alerts
|

Arctic Micromonas uses protein pools and non-photochemical quenching to cope with temperature restrictions on Photosystem II protein turnover

Abstract: Micromonas strains of small prasinophyte green algae are found throughout the world’s oceans, exploiting widely different niches. We grew arctic and temperate strains of Micromonas and compared their susceptibilities to photoinactivation of Photosystem II, their counteracting Photosystem II repair capacities, their Photosystem II content, and their induction and relaxation of non-photochemical quenching. In the arctic strain Micromonas NCMA 2099, the cellular content of active Photosystem II represents only ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…In fact, across our studies to date (Ni et al, 2017; Figure S7) the maximum YNPQ we have consistently observed is ∼0.6 in an arctic strain of the prasinophyte Micromonas. As a conceptual exercise we used the chlorophyllspecific absorption coefficient, corrected for cell size (Fujiki and Taguchi, 2002), and the 35 chlorophyll content of the core of PSII (Umena et al, 2011) to estimate the approximate effective absorption cross section for PSII in the absence of any associated antenna complexes.…”
Section: Figure 4 Presents the Responses Of σ Psiimentioning
confidence: 52%
See 4 more Smart Citations
“…In fact, across our studies to date (Ni et al, 2017; Figure S7) the maximum YNPQ we have consistently observed is ∼0.6 in an arctic strain of the prasinophyte Micromonas. As a conceptual exercise we used the chlorophyllspecific absorption coefficient, corrected for cell size (Fujiki and Taguchi, 2002), and the 35 chlorophyll content of the core of PSII (Umena et al, 2011) to estimate the approximate effective absorption cross section for PSII in the absence of any associated antenna complexes.…”
Section: Figure 4 Presents the Responses Of σ Psiimentioning
confidence: 52%
“…Indeed, for the second derivative of whole cell spectra, we found a difference at 487 nm before and after 8 min of actinic light treatment in Ostreococcus from growth saturating light (Figure S5B), likely reflecting an increase in the de-epoxidised xanthophyll cycle pigment content zeaxanthin (485 nm) (Méléder et al, 2013;Ni et al, 2017). This lightdependent difference at 487 nm was not found in Ostreococcus from growth limiting light (Figure S5A), reflecting a smaller content of xanthophyll cycle pigments.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations